A comparative analysis of the pump controlled, valve controlled and prime mover controlled hydromotor drive to attain constant speed for varying load. (January 2022) - Kushwaha, Prabhakar; Dasgupta, Kabir; Ghoshal, Sanjoy K.
Abstract: The article compares the dynamic performances of the pump-controlled, valve-controlled and prime-mover controlled hydromotor drive systems for a wide range of operating conditions. The control strategy adopted for each of them varies the supply flow to the hydromotor that gives the regulated drive speed. In this respect, the Simscape models are developed for the said systems that are validated experimentally. On the basis of response time, overshoot, and steady-state error obtained from the simulation and test results, it is found that the valve controlled hydromotor drive system is more sensitive than the others; whereas, the load-sensing pump control requires more time to settle but has less overshoot. Highlights: Three different control experiments are carried out to achieve a constant speed of a hydromotor under varying load. The system parameters are estimated and validated by using optimization techniques. It is established that the valve controlled hydromotor drive is more sensitive than others. The load-sensing hydromotor drive is found to have a more sluggish response compared to the others.